2010
DOI: 10.1007/s00125-010-1742-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between mannose-binding lectin, high-sensitivity C-reactive protein and the progression of diabetic nephropathy in type 1 diabetes

Abstract: Aims/hypothesis Diabetic nephropathy has been associated with low-grade inflammation and activation of the complement system in cross-sectional studies. Data from prospective studies are sparse. We investigated the associations of the complement activator mannose-binding lectin (MBL) and the inflammatory marker high-sensitivity C-reactive protein (hsCRP) with the development of nephropathy in a large prospective study of patients with type 1 diabetes from the Finnish Diabetic Nephropathy (FinnDiane) Study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 31 publications
3
57
1
Order By: Relevance
“…The association between MBL and diabetic nephropathy has been observed in several clinical studies (2)(3)(4)(5)(6)(7)(8). Also, the MBL2 genotype in the present cohort was marginally unequally distributed between patients with or without diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The association between MBL and diabetic nephropathy has been observed in several clinical studies (2)(3)(4)(5)(6)(7)(8). Also, the MBL2 genotype in the present cohort was marginally unequally distributed between patients with or without diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have demonstrated the close association between the lectin pathway of complement activation and diabetic nephropathy. In particular, high concentrations of the carbohydrate pattern-recognition molecule mannan-binding lectin (MBL), which initiates complement activation, are linked to diabetic nephropathy defined by urinary albumin excretion rate (2)(3)(4)(5)(6)(7)(8). In the present cohort, we previously showed the cross-sectional association between MBL2 genotype and diabetic nephropathy (2).…”
mentioning
confidence: 56%
“…7,27 This is supported by studies in ischemia-reperfusion injury, rheumatoid arthritis, or diabetic nephropathy, in which high MBL was associated with cardiovascular and renal damage. 10,13,14,30,31 We observed that participants with high plasma MBL had lower cIMT. This confirms a previously reported beneficial role of MBL in vascular integrity in a large study.…”
Section: Discussionmentioning
confidence: 58%
“…In vitro studies have demonstrated that C3a is the [35,36]. Activation of complement, which can lead to the generation of C3a, has also been demonstrated to increase in diabetic nephropathy [37]. Thus, we suggest that increased complement activation might contribute to the recruitment and activation of MCs.…”
Section: Discussionmentioning
confidence: 72%